Mathematik und Mathematikunterricht aus der Sicht von Hauptschülern (mathematica didactica, 2007)
The integration of modelling and applications into the curriculum is seen as a means of improving mathematics education in all schools. Can this approach be adapted successfully within the „Hauptschule“? In order to develop teaching concepts appropriate to the conditions of the Hauptschule, a survey about students’ mathematical beliefs has been carried out within a qualitative empirical study. The paper describes the theoretical and methodological framework as well as the results of the study. Two case-examples, a survey of the reconstructed beliefs and a typology is presented.